EFFECT OF PLASTIC MULCHING AND PESTICIDE APPLICATION ON ACTIVE AND STABLE CARBON IN VOLCANIC SOILS, WEST SUMATRA - Maulana Kamil; Annisa Rachim; Irwin Mirza Umami; Khairun Nisa Kamarudin; Hermansah Hermansah (BPFP Universitas Bengkulu, 2023)
Agricultural intensification plays an important role in sustaining productivity. Plastic mulching and the application of pesticides in crop cultivation have become inevitable to achieve high yield production. This study was aimed to determine the effect of plastic mulching and pesticide applications on carbon (C) fractions. The field experiment was designed using a completely randomized design with two factors consisting of plastic mulching and the application of pesticide at two levels (with and without) at each treatment. All the treatments were prepared for three replications. The soil carbon fractions data collected includes active C and humic acid as stable C fractions. The findings of this research showed that both active and stable C fractions were not significantly influenced by plastic mulching and pesticide applications. The active and stable C fractions were ranging from 1.40 to 1.42 g/kg and from 193.3 to 220 g/kg, respectively. These results might be attributed to the period of the study. The duration of this study might be not sufficient to capture any potential long-term changes in soil C fractions induced by the treatments. Thus, further research should consider extending the experiment duration to assess the long-term effects of the agricultural practices to C fractions.